2017
DOI: 10.1159/000477267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Challenges in Upper Gastrointestinal Malignancies after Bariatric Surgery

Abstract: Background/Aims: The incidence of morbid obesity has exponentially increased over the last decades. Bariatric surgery (BS) has been proven effective in inducing weight loss and resolving comorbidities associated with morbid obesity. However, BS can also lead to major diagnostic and treatment challenges in patients who develop upper gastrointestinal malignancies. It is important to create awareness of this rising problem. Methods: Relevant literature was searched in PubMed. Results: (Formerly) obese patients ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…A population-based cohort study among individuals with an obesity diagnosis showed a worse rectal cancer prognosis among those who had undergone bariatric surgery; however, weaknesses of the study include the limited sample size ( n = 131 patients who were obese and underwent bariatric surgery with colorectal cancer) and the lack of adjustment for tumour stage 23 . Another emerging issue is that alterations in gastrointestinal anatomy resulting from bariatric surgery can lead to different presentation of symptoms, thus making diagnosis of cancer more challenging 24 .…”
Section: Interventions For Cancer Preventionmentioning
confidence: 99%
“…A population-based cohort study among individuals with an obesity diagnosis showed a worse rectal cancer prognosis among those who had undergone bariatric surgery; however, weaknesses of the study include the limited sample size ( n = 131 patients who were obese and underwent bariatric surgery with colorectal cancer) and the lack of adjustment for tumour stage 23 . Another emerging issue is that alterations in gastrointestinal anatomy resulting from bariatric surgery can lead to different presentation of symptoms, thus making diagnosis of cancer more challenging 24 .…”
Section: Interventions For Cancer Preventionmentioning
confidence: 99%
“…Obesity has a systemic carcinogenic effect, resulting in an increased risk of developing cancer in various organs, such as liver, pancreas and stomach [ 7 ]. Although the underlying mechanisms are not completely elucidated, various theories have been proposed, such as pro-inflammatory effect due to metabolic syndrome, chronic hyperinsulinemia exposing preneoplastic cells to tumorigenic effects and development of insulin resistance [ 9 , 12 ]. The weight loss obtained after BS also seems to be responsible for the reduced risk of cancer in these patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports of GC in the ES, occurring 5–22 years after surgery [ 6 , 8 ]. The diagnosis is challenging since there is no access to perform upper gastrointestinal endoscopy (UGE) in the ES and the symptoms are nonspecific [ 9 , 10 ]. The most important preventive measure is the systematic preoperative risk assessment, with a detailed evaluation of familial history, patients’ conditions and UGE for assessment of the presence of H. pylori [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, gastroesophageal reflux disease and BE are identified risk factors for UGI malignancies, commonly lower esophageal cancers [63,64]. Vague UGI symptoms after bariatric surgery, such as nausea, dysphagia, or reflux, may cause delayed cancer diagnosis, as these can be common postbariatric surgery complaints; this can result in more advanced tumors at the time of diagnosis [65]. Periodic endoscopic surveillance in patients with known BE and early evaluation in patients who develop new symptoms, such as upper abdominal pain, dysphagia, reflux, or anemia, after bariatric surgery are also strongly encouraged [66].…”
Section: Upper Gastrointestinal Cancermentioning
confidence: 99%
“…After sleeve gastrectomy (SG), it is impossible to use the stomach for reconstruction after esophagectomy. In such circumstances, an esophagojejunostomy or colon interposition is necessary, likely increasing postoperative morbidity [65]. In cases of esophageal cancer after prior RYGB, experienced surgeons advise a close collaboration between bariatric and cancer surgeons to address a technically nuanced complex procedure for cancer resection and reconstruction [69].…”
Section: Upper Gastrointestinal Cancermentioning
confidence: 99%